Algoritma Hopfield dalam menentukan rute tercepat untuk pendistribusian telur kepada konsumen - Priyatno, Gregorius Algananda Hartanto; Romadhona, Rizki Dwi (Universitas Merdeka Malang, 2023)
ENJ Poultry Shop is a business that operates in the field of egg distribution. The main problem faced is determining delivery routes, which are still less effective. The focus of this research is optimization to determine the fastest route through implementing the Hopfield algorithm in the application. With the Hopfield algorithm, it is hoped that it can provide a solution for finding the shortest route to distribute eggs to consumers. This research is quantitative, where the analysis is carried out by comparing the results of manual calculations with the results of calculations using the application. Data collection was carried out at a number of locations, which were used as delivery destination addresses. The Hopfield algorithm is applied by determining the delivery point to be addressed, then measuring each delivery distance so that an estimate of the distance at each point is obtained. After obtaining all the data, it is continued with calculations using the Hopfield algorithm. Based on the research results, it can be concluded that the implementation of the application works better, resulting in the fastest distance and time in determining the egg delivery route. By optimizing distribution time, it is possible to increase marketing and provide consumer satisfaction.